2021
DOI: 10.3390/ijms22115612
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids—A Review of Their Toxicity to Living Organisms

Abstract: Ionic liquids (ILs) were initially hailed as a green alternative to traditional solvents because of their almost non-existent vapor pressure as ecological replacement of most common volatile solvents in industrial processes for their damaging effects on the environment. It is common knowledge that they are not as green as desired, and more thought must be put into the biological consequences of their industrial use. Still, compared to the amount of research studying their physicochemical properties and potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 174 publications
(203 reference statements)
0
69
0
Order By: Relevance
“…The issue with assessing the greenness of ILs is that reports and safety data sheets typically refer to physicochemical properties such as density and viscosity [9,10,13]. Unfortunately, data related to toxicity, biodegradability, and other environmental parameters are still scarce.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue with assessing the greenness of ILs is that reports and safety data sheets typically refer to physicochemical properties such as density and viscosity [9,10,13]. Unfortunately, data related to toxicity, biodegradability, and other environmental parameters are still scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have found that the majority of ILs are not easily biodegradable and are relatively toxic. Consequently, the lack of data on the biodegradability of ILs poses a serious problem in determining the hazard status and safer characteristics of the ILs when performing environmental evaluations to determine their greenness [12][13][14]. In order to assess the 'green' credentials of the ILs, a strategy must be implemented that takes into account market demands as well as health, safety, and environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…The reputation of these solvents as “environmentally friendly” chemicals is mainly based on their insignificant vapor pressure. However, the solubility of ILs in water and a number of reports documenting the toxicity of ILs for aquatic organisms highlight a real cause for concern [ 51 ]. The importance of ILs in medical and pharmaceutical applications is now relevant, and it has already been realized that its antimicrobial and cytotoxic activity may have several benefits in the future.…”
Section: Nanofluids and Ionanofluidsmentioning
confidence: 99%
“…Several studies on cytotoxicity of ILs towards various cell lines are nowadays available, e.g., with human keratinocyte cell line HaCaT [ 105 ], colorectal adenocarcinoma cell lines CaCo-2 [ 188 , 189 ] and HT29 [ 29 , 190 ], and human cervical carcinoma cell line HeLa [ 191 , 192 ]. The accumulated IL cytotoxicity data, ranging from micromolar (or even nanomolar) to millimolar scales, suggest the main dependence on their chemical structure despite the important role played by the cell line (for recent reviews on the topic refer to [ 14 , 193 , 194 ]). Structural modifications at the level of the ILs’ ions can be somehow correlated with their cytotoxicity, allowing to establish general guidelines on how to design more biocompatible ILs.…”
Section: Key Factors In Choosing Hydrophilic Ils In Fields Involving Pharmaceuticalsmentioning
confidence: 99%
“…These features together with their high solvation aptitude for a plethora of molecules placed ILs as useful tools for manufacturing processes in the pharmaceutical industry (e.g., in recovery and purification processes) and sample preparation techniques. The solubility in water of most ILs (at least to some degree), especially that of hydrophilic ILs, together with their toxicological features, highlighted their potential to enter the environment and negatively affect ecosystems [ 14 , 193 ]. Under this scenario, ILs are currently classified as emerging contaminants like other well-known pollutants, such as perfluorinated alkyl compounds [ 206 ].…”
Section: Key Factors In Choosing Hydrophilic Ils In Fields Involving Pharmaceuticalsmentioning
confidence: 99%